Inequalities between settlements from touristic point of view - Oláh, Izabella; Áldorfai, György; Béres-Virág, Ágnes (Studia Mundi – Economica, 2017)
In recent years, numbers of tourist trips and guests have been increasing in Hungary, so the tourism revenues were increased significant. The smaller, rural settlements are considered tourism an outbreak point based on endogenous resources, which can be overcome by economic and territorial differences. In our study, we investigate the territorial disparities with several methods and analyze the tourist opportunities of the settlements with population below 1,000 people.